The Development and Evolution of Kalam Discussions in the Indian Subcontinent: An Exploration of Islamic Theological Debates - Dr. Hafiz Muhammad Tahir Al Mustafa (Journal of World Religions and Interfaith Harmony, 2024)
This research undertakes a comprehensive examination of the development and evolution of kalam discussions in the Indian subcontinent, with a specific focus on Pakistan and India. Kalam, a vital component of Islamic theology, has undergone significant transformations in the region, shaped by historical, cultural, and intellectual factors. Through a critical analysis of primary sources, including theological treatises, commentaries, and debates, this study traces the trajectory of kalam discussions from the early Islamic period to the 19th century. It explores the contributions of influential scholars, the emergence of distinct theological schools, and the engagement with philosophical and mystical ideas. This research reveals the dynamic and diverse nature of Islamic theological thought in the Indian subcontinent, highlighting its ongoing relevance and significance in contemporary Muslim intellectual discourse. By shedding light on the evolution of kalam discussions, this study aims to enhance our understanding of Islamic theology, its historical development, and its continued impact on Muslim thought and culture.